The prevalence, incidence and prevention of Plasmodium falciparum infections in forest rangers in Bu Gia Map National Park, Binh Phuoc province, Vietnam: a pilot study. - Son, D; Thuy-Nhien, N; von Seidlein, L; Le Phuc-Nhi, T; Phu, N; Tuyen, N; Tran, N; Van Dung, N; Van Quan, B; Day, N; Dondorp, A; White, N; et al. (BioMed Central, 2017)
Background Prophylaxis for high-risk populations, such as forest workers, could be one component for malaria elimination in the Greater Mekong Sub-region. A study was conducted to assess the malaria incidence in forest rangers and the feasibility of malaria prophylaxis for rangers sleeping in forest camps. Methods Forest rangers deployed in the Bu Gia Map National Park, Vietnam were invited to participate in the study. Plasmodium infections were cleared using presumptive treatment, irrespective of malaria status, with a 3-day course dihydroartemisinin/piperaquine (DP) and a 14-day course of primaquine. Before returning to the forest, study participants were randomly allocated to a 3-day course of DP or placebo. Fifteen days after returning from their forest deployment the participants were tested for Plasmodium infections using uPCR. Results Prior to treatment, 30 of 150 study participants (20%) were found to be infected with Plasmodium. Seventeen days (median) after enrolment the rangers were randomized to DP or placebo 2 days before returning to forest camps where they stayed between 2 and 20 days (median 9.5 days). One ranger in the DP-prophylaxis arm and one in the placebo arm were found to be infected with Plasmodium falciparum 15 days (median) after returning from the forest. The evaluable P. falciparum isolates had molecular markers indicating resistance to artemisinins (K13-C580Y) and piperaquine (plasmepsin), but none had multiple copies of pfmdr1 associated with mefloquine resistance. Conclusion Anti-malarial prophylaxis in forest rangers is feasible. The findings of the study highlight the threat of multidrug-resistant malaria.